2013
DOI: 10.1111/age.12055
|View full text |Cite
|
Sign up to set email alerts
|

Association of a single nucleotide polymorphism in the akirin 2 gene with economically important traits in Korean native cattle

Abstract: The akirin 2 gene, located on chromosome 9 in cattle, was previously reported to be associated with nuclear factor-kappa B (NF-κB), involved in immune reactions and marbling of meat. To determine whether a single nucleotide polymorphism (SNP) in akirin 2 is associated with economically important traits of Korean native cattle, the c.*188G>A SNP DNA marker in the 3'-UTR region of akirin 2 was analyzed for its association with carcass weight, longissimus muscle area and marbling. The c.*188G>A SNP was genotyped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 21 publications
1
22
1
Order By: Relevance
“…However, none of these has been associated with variations in androstenone levels. This is in contrast to new results indicated that single nucleotide polymorphisms in the full-length gene have an impact on the accumulation of androstenone in Duroc pigs [120]. …”
Section: The Boar Taint Phenomenoncontrasting
confidence: 90%
“…However, none of these has been associated with variations in androstenone levels. This is in contrast to new results indicated that single nucleotide polymorphisms in the full-length gene have an impact on the accumulation of androstenone in Duroc pigs [120]. …”
Section: The Boar Taint Phenomenoncontrasting
confidence: 90%
“…In recent years, with the significant expansion of the genomic sequence data in many aquaculture species, more and more studies have focus on the identification of SNPs in aquaculture species (Hayes, Laerdahl, Lien, Moen, Berg, Hindar, Davidson, Koop, Adzhubei & Høyheim 2007;Ciobanu, Bastiaansen, Magrin, Rocha, Jiang, Yu, Geiger, Deeb, Rocha, Gong, Kinghorn, Plastow, Van der Steen & Mileham 2010;Li, He, Yang, Shan, Tan & Gao 2010;Van Bers, Crooijmans, Groenen, Dibbits & Komen 2012). However, the association studies between the SNPs and the production traits for most aquaculture species, especially for the Chinese mitten crab, are still limited comparing with that in other domestic animals (Clop, Marcq, Takeda, Pirottin, Tordoir, Bib e, Bouix, Caiment, Elsen, Eychenne, Larzul, Laville, Meish, Milenkovic, Tobin, Charlier & Georges 2006;Daga et al 2013;Glatzer et al 2013;Kim et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these genes could be considered as important candidate genes for growth-related traits in beef cattle. Furthermore, the c.*188G > A single nucleotide polymorphism (SNP) in AKIRIN2, the g.231054C > T SNP in TTN, the g.1471620G > T SNP in EDG1, and the g.70014208A > G SNP in the MYBPC1 genes showed associations of these SNPs with growth-related traits in JB [13][14][15][16][17][18] and Korean native (KN) [19] cattle. However, the relationships of these SNPs with growth-related traits in Chinese cattle breed have not been investigated.…”
Section: Introductionmentioning
confidence: 99%